Manfaat dan Hambatan Penerapan Hazard Analysis and Critical Control Points (HACCP) pada UMKM produk pangan di Indonesia: Kajian Literatur (International Forum of Researchers and Lecturers, 2025)
Hazard Analysis and Critical Control Points (HACCP) is a food safety management system designed to identify, analyze, and control physical, chemical, and biological hazards throughout the food production process. In the context of Small, and Medium Enterprises (SMEs) in Indonesia, HACCP implementation is essential to ensure food safety, improve product quality, and enhance access to modern and export markets. This study is a literature review that analyzes 14 scientific articles published between 2000 and 2025, sourced from Scholar and Sinta databases. The analysis focused on abstract keywords to identify key concepts, findings, and research gaps regarding HACCP implementation in SMEs food businesses. The review findings indicate that HACCP offers positive impacts such as improved production efficiency, extended shelf life, and reduced contamination risks. The establishment of Critical Control Points (CCPs) in stages like grinding, packaging, and storage has proven effective in preventing potential hazards. However, several challenges hinder effective implementation, particularly in SMEs. Common obstacles include limited human resources, lack of technical knowledge, inadequate basic sanitation infrastructure, and weak documentation and monitoring systems. Several studies also emphasize that successful HACCP implementation relies heavily on intensive mentoring and strong support from government bodies, academia, and business partners. Therefore, a collaborative and strategic approach is essential to optimize HACCP implementation within the SMEs sector, contributing to an inclusive, adaptive, and sustainable national food safety system.